You must be very intelligent : the PhD delusion - Bodewits, Karin (Springer, 2017)
You Must be Very Intelligent is the author's account of studying for a PhD in a modern, successful university. Part-memoir and part-exposé, this book is highly entertaining and unusually revealing about the dubious morality and desperate behaviour which underpins competition in twenty-first century academia. When Karin enters a high-ranked university to start her PhD she is brimming with hope and positively overflowing with grit determination to prove she is worthy. After all, she knows that only the extraordinarily learned and the astonishingly intelligent ever hold chairs and professorships ... She knows researchers are idealists yearning to enrich the stock of human knowledge ... She knows university is the apotheosis of civilised culture ... She knows ... very little ... This witty, warts-and-all tale of postgrad life in the august University of Edinburgh will strike a chord in anyone who has ever aspired to life in the ivory tower. It is a warm-hearted story of disillusionment, wherein passion and innocence are merrily bludgeoned by big egos, ludicrous farce, tawdry corruption, pimped-out brains and the sheer unreality of trying to be a grown-up in a brat's world ... This is Karin's humorous story, but it is also the tragic story of the modern European university system; where money and power are the amoral Gods, and the noble search for truth quietly atrophies.
Keywords: Doctor of philosophy degree -- Fiction.; Degrees, Academic -- Fiction.; elektronické knihy; electronic books